Fanfiction jako mediacja – propozycja dydaktyzacji na użytek lekcji języka obcego - Pudo, Dorota (Neofilolog, 2026)
Mediation is an important language activity first introduced to the Second Language Acquisition field (SLA) through the Common European Framework of Reference (CEFR) in 2001 and further developed in subsequent years. In this article, we explore the relationship between mediation and fanfiction, an extracurricular fan practice that transforms popular cultural artifacts into fictional texts shared in dedicated online spaces. We argue that, although creating fanfiction may appear to be a productive activity at first glance, its inherently transformative nature makes it a particularly effective tool for practicing mediation. As practiced by fans, fanfiction writing involves a thorough reception of the original cultural text, the development of a personal interpretation of it, the anticipation of the needs and reactions of a potential audience (other fans), and the crafting of a text that is original yet firmly grounded within the fictional universe of its source. The article presents examples of foreign language tasks involving fanfiction prompts, focusing on their potential to practice mediation, as well as proporses criteria for their evaluation.